Protective structure and preparation method and application thereof
Patent Information
- Application Number
- CN202510882046.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-27
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-06-27
AI Technical Summary
[0004]能量耗散机制有限:传统UHPC主要依靠高密实度和高强度骨料抵抗侵彻,其主要耗能机制为基体的微裂纹扩展和钢纤维的桥接作用;但由于UHPC基体较脆,裂缝扩展速度快,能量耗散能力有限,导致裂纹垂直于迎弹面的扩展尺寸大,即侵彻深度较大
1.本发明基于应力波的产生和传递过程设计了多层梯度结构;抗裂层采用自修复材料、混杂纤维和定向钢纤维复合增强,在承受侵彻过程中压缩波和拉伸波共同作用下的复杂应力状态时,能够有效抑制初始破坏、延缓裂纹扩展并实现局部自修复;过渡层利用纤维织物具有高柔性和多孔特性,可在冲击波作用下提供缓冲,从而削弱冲击波的连续性,减少冲击波在层间的传递强度,提高整体抗冲击能力;抗穿透层采用多级骨科梯度优化设计的掺粗骨料超高性能混凝土(UHPC-CA),通过不同粒径及强度的骨料组合,提高材料密实度及抗侵彻性能,从而显著降低弹体穿透深度;吸能层减少冲击波的传递,降低下层结构损伤。吸能材料通过变形、破碎或内部能量耗散机制能有效衰减冲击波,提高后续层的防护效果;抗剥落层采用自修复材料与PE纤维复合增强,抑制侵彻过程中拉伸波引发的表层剥落破坏,提高结构耐久性和整体防护能力。使各层材料特性与应力波的产生和传递过程高度匹配,各层之间协同作用,实现抗裂、吸能、抗穿透、冲击耗散及抗剥落等多重防护功能,从而大幅增强整体抗侵彻能力。
Smart Images

Figure CN120620778B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, and in particular to a protective structure, its preparation method, and its application. Background Technology
[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
[0003] With the advancement of weaponry technology, the need for protection of buildings and facilities has become increasingly urgent. Enhancing the penetration resistance of building materials has become an important research direction in the field of protective engineering. Ultra-High Performance Concrete (UHPC), due to its high strength, high toughness, and durability, is widely used in military protection, nuclear safety facilities, and special engineering structures. In the field of penetration resistance, traditional UHPC mainly relies on the high strength characteristics of a single material, but it still has the following shortcomings when facing high-speed projectile impacts.
[0004] Limited energy dissipation mechanism: Traditional UHPC mainly relies on high density and high strength aggregates to resist penetration. Its main energy dissipation mechanism is the propagation of microcracks in the matrix and the bridging effect of steel fibers. However, due to the brittleness of the UHPC matrix and the fast crack propagation speed, the energy dissipation capacity is limited, resulting in a large crack propagation size perpendicular to the impact surface, i.e. a large penetration depth.
[0005] Poor interlayer compatibility: Existing multi-layer penetration-resistant concrete usually adopts strength-gradient or function-gradient design, but the interlayer bonding interface compatibility is poor, which can easily lead to delamination and spalling due to shear failure, thus reducing the overall protective performance.
[0006] Lack of dynamic self-healing ability: After traditional UHPC is subjected to penetration damage, the cracks are difficult to repair themselves, which leads to the gradual decline of the mechanical properties of the material and affects the long-term service capability of the structure. Summary of the Invention
[0007] To address the shortcomings of existing technologies, the present invention aims to provide a protective structure, its preparation method, and its application. By constructing a multi-layered gradient structure, the material properties of each layer are matched with the generation and transmission process of stress waves. At the same time, an impact-triggered self-healing system is introduced to achieve synergistic protection against different types of penetration damage, thereby significantly improving the material's comprehensive penetration resistance, impact energy dissipation capacity, and structural integrity, and enhancing long-term service performance.
[0008] To achieve the above objectives, the present invention is implemented through the following technical solution: The first aspect of the present invention provides a protective structure comprising, from the outside in, a crack-resistant layer, a transition layer, a penetration-resistant layer, an energy-absorbing layer, and a peel-resistant layer; The raw materials for preparing the transition layer include: fiber fabric, 2-3 parts by weight of epoxy resin, and 0.5-1.5 parts by weight of chopped basalt fibers; The energy-absorbing layer includes an energy-absorbing material; The raw materials for preparing the crack-resistant layer, penetration-resistant layer and spalling-resistant layer include the following components in parts by weight: 360-520 parts cement, 36-52 parts silica fume, 36-52 parts fly ash, 800-1000 parts fine aggregate, 120-130 parts water and 5-10 parts high-efficiency water-reducing agent. The crack-resistant layer comprises 156-312 parts of straight steel fiber, 39-78 parts of PE fiber, and 12-16 parts of self-healing microcapsules; The anti-penetration layer comprises 800-1000 parts of coarse aggregate and 39-78 parts of hook-shaped steel fiber; The anti-peeling layer comprises 12-16 parts of PE fiber mesh and self-healing microcapsules.
[0009] Secondly, the method for preparing the aforementioned protective structure includes the following processes: S1. After dry mixing of cement, silica fume, fly ash and fine aggregate, water and water-reducing agent are added. During wet mixing, self-healing microcapsules are added. After mixing, straight steel fibers and PE fibers are added respectively. The mixture is then poured into a mold to obtain a crack-resistant layer. S2. Before the crack-resistant layer initially sets, the fiber fabric impregnated with epoxy resin is laid on the surface of the crack-resistant layer and rolled. After rolling, basalt short-cut fibers are embedded to obtain a transition layer. S3. Mix the moistened coarse aggregate, fine aggregate, cement, silica fume and fly ash dry, then add water and water-reducing agent. During the wet mixing process, add end-hook steel fibers. After mixing evenly, pour the mixture onto the surface of the transition layer to obtain an anti-penetration layer and sandblast it. S4. Apply adhesive to the surface of the energy-absorbing material that is in contact with the anti-penetration layer, then hot-press the energy-absorbing material onto the surface of the anti-penetration layer, and apply adhesive to the surface of the energy-absorbing material to obtain the energy-absorbing layer. S5. After dry mixing cement, silica fume, fly ash and fine aggregate, add water and water-reducing agent. During wet mixing, add self-healing microcapsules. Then pour it above the energy-absorbing layer. During the pouring process, lay PE fiber mesh so that the PE fiber mesh is located in the middle of the pouring to form an anti-stripping layer. After curing, a protective structure is obtained.
[0010] Thirdly, the present invention provides the application of the above-mentioned protective structure.
[0011] The beneficial effects of this invention are as follows: 1. This invention designs a multi-layered gradient structure based on the generation and transmission process of stress waves. The crack-resistant layer is reinforced with self-healing materials, hybrid fibers, and directional steel fibers. When subjected to complex stress states under the combined action of compressive and tensile waves during penetration, it can effectively suppress initial damage, delay crack propagation, and achieve local self-repair. The transition layer utilizes the high flexibility and porous properties of fiber fabrics to provide buffering under the action of shock waves, thereby weakening the continuity of shock waves, reducing the transmission intensity of shock waves between layers, and improving the overall impact resistance. The penetration-resistant layer adopts ultra-high performance concrete (UHPC-CA) with coarse aggregate and optimized design based on multi-level orthopedic gradient. By combining aggregates with different particle sizes and strengths, the material density and penetration resistance are improved, thereby significantly reducing the penetration depth of the projectile. The energy-absorbing layer reduces the transmission of shock waves and reduces damage to the underlying structure. Energy-absorbing materials effectively attenuate shock waves through deformation, fragmentation, or internal energy dissipation mechanisms, enhancing the protective effect of subsequent layers. The anti-stripping layer, reinforced with self-healing materials and PE fibers, suppresses surface spalling damage caused by tensile waves during penetration, improving structural durability and overall protection. This ensures a high degree of matching between the material properties of each layer and the generation and transmission process of stress waves, with each layer working synergistically to achieve multiple protective functions such as crack resistance, energy absorption, penetration resistance, impact dissipation, and spalling resistance, thereby significantly enhancing overall penetration resistance.
[0012] 2. Self-healing microcapsules are added to the crack-resistant layer and the spalling-resistant layer of the present invention, and an impact-triggered self-healing system is adopted. After being impacted, the self-healing microcapsules actively release the repair agent, quickly fill the microcracks, improve the damage resistance of concrete, significantly extend the service life of the material, and ensure the long-term stability of the structure.
[0013] 3. In the preparation process, the present invention adopts directional steel fiber composite reinforcement technology, which promotes the directional arrangement of straight steel fibers and further improves the toughness of the crack-resistant layer. Attached Figure Description
[0014] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0015] The diagram exaggerates the spacing or dimensions between parts to show their positions; the diagram is for illustrative purposes only.
[0016] Figure 1 This is a schematic diagram of the protective structure in Example 1.
[0017] Figure 2 This is a flowchart illustrating the preparation process of the protective structure in Example 1.
[0018] Figure 3This is a schematic diagram of the interlayer transmission of stress waves generated by the target when the projectile penetrates during Example 1. Detailed Implementation
[0019] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0020] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0021] The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0022] A typical embodiment of the present invention provides a protective structure comprising, from the outside in, a crack-resistant layer, a transition layer, a penetration-resistant layer, an energy-absorbing layer, and a peel-resistant layer; The raw materials for preparing the crack-resistant layer, penetration-resistant layer and spalling-resistant layer include the following components in parts by weight: 360-520 parts cement, 36-52 parts silica fume, 36-52 parts fly ash, 800-1000 parts fine aggregate, 120-130 parts water and 5-10 parts high-efficiency water-reducing agent. The crack-resistant layer also includes 156-312 parts of straight steel fiber, 39-78 parts of PE fiber, and 12-16 parts of self-healing microcapsules; The anti-penetration layer also includes 800-1000 parts of coarse aggregate and 39-78 parts of hook-shaped steel fiber; The anti-peeling layer also includes 12-16 parts of PE fiber mesh and self-healing microcapsules; The raw materials for preparing the transition layer include: 1 part by weight of fiber fabric, 2-3 parts by weight of epoxy resin, and 0.5-1.5 parts by weight of chopped basalt fibers; The energy-absorbing layer includes an energy-absorbing material.
[0023] In the above structure, the crack-resistant layer uses hybrid fibers, selecting fibers of different sizes and types to enhance overall toughness. PE fibers, with their high elongation at break and excellent bridging ability, improve the material's tensile toughness. Under the complex stress state of combined compressive and tensile waves during penetration, it effectively inhibits crack initiation and delays crack propagation. Meanwhile, the microcapsules actively release repair agents upon impact, rapidly filling microcracks and further improving the concrete's damage resistance. The transition layer utilizes the high flexibility and porosity of fiber fabrics to provide buffering under shock wave action, weakening shock wave continuity and reducing the intensity of interlayer shock wave transmission. The penetration-resistant layer uses UHPC-CA to improve material density and impact resistance, thereby effectively reducing the projectile's penetration depth. The energy-absorbing layer uses energy-absorbing materials that effectively attenuate shock waves through deformation, fragmentation, or internal energy dissipation mechanisms, reducing damage to the underlying structure. The anti-stripping layer uses PE fiber composite reinforcement technology, which effectively suppresses surface spalling damage caused by tensile waves during penetration, further enhancing the overall protective capability of the material. Similar to the crack-resistant layer, the anti-stripping layer utilizes the high elongation at break and excellent bridging ability of PE fibers to improve the tensile toughness of the material. Meanwhile, the microcapsules actively release repair agents after being impacted, which can quickly fill microcracks and further improve the damage resistance of concrete.
[0024] Optionally, the thickness of the crack-resistant layer is 20-50 mm, the thickness of the transition layer is 1-4 mm, the thickness of the penetration-resistant layer is 80-150 mm, the thickness of the energy-absorbing layer is 10-20 mm, and the thickness of the anti-stripping layer is 20-50 mm.
[0025] Optionally, the straight steel fibers in the crack-resistant layer are oriented perpendicular to the surface of the protective structure, thereby further enhancing the tensile strength and crack suppression effect of the matrix through directional arrangement.
[0026] Optionally, the straight steel fibers include straight steel fibers with lengths of 6mm, 13mm and 20mm, and the mass ratio of the three is 1:(0.5~1.5):(0.5~1.5); the steel fibers of different lengths form multiple mechanical constraints inside the material, effectively improving the crack resistance and delaying the crack propagation process.
[0027] Optionally, the coarse aggregate includes basalt and corundum in a mass ratio of (5~6):(4~5), wherein the basalt has a particle size of 5~8mm and the corundum has a particle size of 3~5mm; by combining aggregates with different particle sizes and strengths, the density and penetration resistance of the material can be further improved.
[0028] Optionally, the fine aggregate includes natural river sand and steel grit in a mass ratio of (5~7):(3~5), which has higher hardness to improve the density of the material.
[0029] Optionally, the energy-absorbing layer is connected to the anti-penetration layer and the anti-stripping layer respectively by an adhesive, wherein the adhesive is an epoxy resin adhesive, and a hot-pressing process is used to ensure that the energy-absorbing layer is tightly bonded to the anti-penetration layer and the anti-stripping layer.
[0030] Optionally, the energy-absorbing material includes one or more of polyurethane elastic material and nitrile rubber, wherein the hardness of the polyurethane elastic material is Shore A 70~90, and the loss factor tanδ of the nitrile rubber is ≥0.3, making it a high-energy-absorbing material.
[0031] Optionally, 1 to 3 parts of curing agent are added to the crack-resistant layer and the peel-resistant layer. The curing agent is an epoxy resin amine curing agent, which is added in combination with the self-healing microcapsule, and the amount added is 10 to 15% of the mass of the self-healing microcapsule.
[0032] Optionally, the self-healing microcapsules are microcapsules formed by encapsulating dicyclopentadiene inside a urea-formaldehyde resin shell, with an average particle size of 50~200μm and a urea-formaldehyde resin shell wall thickness of 5~10μm, forming an impact-triggered self-healing system that releases repair components during the microcrack propagation stage to fill the microcracks.
[0033] Optionally, the fiber fabric has a weight of ≥300g / m². 2 The geotextile is flexible and porous. It is pre-impregnated with epoxy resin emulsion and dried at 60°C until touch dry. The thickness of the epoxy resin residue on the surface is 50~80μm.
[0034] Optionally, the basalt short-cut fibers have an average length of 15 mm and an average diameter of 13 μm, serving as anchors to connect the transition layer and the anti-penetration layer.
[0035] Optionally, the PE fiber is ultra-high molecular weight polyethylene fiber.
[0036] Optionally, the straight steel fibers and the PE fibers are uniformly distributed in the crack-resistant layer.
[0037] Optionally, the PE fiber mesh is a 3D woven PE fiber mesh with a mesh size of (4~6)×(4~6)mm.
[0038] A typical embodiment of the present invention provides a method for preparing the above-mentioned protective structure, comprising the following steps: S1. After dry mixing of cement, silica fume, fly ash and fine aggregate, water and water-reducing agent are added. During wet mixing, self-healing microcapsules are added. After mixing, straight steel fibers and PE fibers are added respectively. The mixture is then poured into a mold to obtain a crack-resistant layer. S2. Before the crack-resistant layer initially sets, fiber fabric impregnated with epoxy resin is laid on the surface of the crack-resistant layer and heated and rolled. Then, basalt short-cut fibers are pre-embedded to obtain a transition layer. S3. The moistened coarse aggregate is mixed with fine aggregate, cement, silica fume and fly ash in a dry mix, and then water and water-reducing agent are added. During the wet mixing process, hooked steel fibers are added. After mixing evenly, the mixture is poured onto the surface of the transition layer to obtain an anti-penetration layer. S4. Apply adhesive to the surface of the energy-absorbing material that is in contact with the anti-penetration layer, then hot-press the energy-absorbing material onto the surface of the anti-penetration layer, and apply adhesive to the surface of the energy-absorbing material to obtain the energy-absorbing layer. S5. After dry mixing of cement, silica fume, fly ash and fine aggregate, water and water-reducing agent are added. Self-healing microcapsules are added during wet mixing. Then, it is poured on top of the energy-absorbing layer. During the pouring process, PE fiber mesh is laid so that the PE fiber mesh is located in the middle of the pouring thickness to form an anti-stripping layer. After curing, a protective structure containing functionally graded anti-penetration self-healing ultra-high performance concrete is obtained.
[0039] Optionally, in S1, the dry mixing time is 4±0.5 min, the stirring speed is 100~150 rpm, and after adding the self-healing microcapsules and the curing agent, the stirring speed is reduced to 50~80 rpm to prevent the self-healing microcapsules from breaking. When the breakage rate of the self-healing microcapsules exceeds the standard, 5% of the original total amount of self-healing microcapsules is added, and the stirring speed is further reduced to below 40 rpm.
[0040] Optionally, in S1, after adding straight steel fibers and PE fibers, the mixture is stirred at a stirring speed of 30~50 rpm until uniform. After casting, the direction of the straight steel fibers is made perpendicular to the surface of the protective structure by a magnetic field orientation method. The magnetic field strength is 0.5~1.2T and lasts for 5~7 minutes, so that the orientation degree of the straight steel fibers is >85%.
[0041] Optionally, in S1, vibration is performed after pouring. The vibration direction includes: vertical vibration to remove large air bubbles, which helps the fine fibers to be evenly distributed in the concrete; followed by vibration at a 15° angle. Since the fiber length direction changes to be perpendicular to the horizontal plane, the tilted vibration can further adjust the fiber length direction, forming a three-dimensional arrangement. This allows the fibers to be appropriately adjusted in the depth direction, avoiding the fibers being arranged only in a plane, which would result in local areas being too dense or too sparse. Therefore, the fibers oriented by the magnetic field before vibration are basically arranged in a two-dimensional direction along the direction of the magnetic field and have not yet been completely dispersed into three-dimensional space. The vibration process helps the fibers to further enter the three-dimensional space arrangement by changing the internal pressure and vibration direction of the concrete. In particular, vibration at an inclined angle can break the original two-dimensional arrangement pattern, making the distribution of fibers in different directions more uniform and adjusting the spatial structure of the fibers.
[0042] Optionally, in S2, the heating temperature is 55~65℃, rolling is performed 2~3 times, the pressure is not less than 0.2MPa, and the temperature is maintained until the surface is dry.
[0043] In S2, the pre-embedding method is surface spreading, so that the basalt short-cut fibers are partially embedded in the crack-resistant layer and partially exposed, so that they play a mechanical anchoring role between the transition layer and the subsequently poured anti-penetration layer.
[0044] Optionally, in S3, the moistened coarse aggregate and 50% of the fine aggregate are first dry-mixed for 3-5 minutes, and then the cementitious material and the remaining fine aggregate are added separately and stirred until uniform; then water and water-reducing agent are added and stirred until uniform.
[0045] Optionally, in S3, after the anti-penetration layer is cured, the surface is sandblasted to improve the bonding strength with the energy-absorbing layer. During the sandblasting process, corundum sand with a particle size of 0.3 mm is used, and the sandblasting air pressure is not less than 0.6 MPa, forming a rough surface with a roughness Ra=50~70 μm.
[0046] Optionally, in S3, after sandblasting, an interface agent is sprayed onto the surface of the anti-penetration layer. The interface agent is a nano-clay modified epoxy resin interface agent with a spraying thickness of 200~300μm. After spraying, it is cured at 60~70℃ for 30~40min to form a uniform and strong interface layer, which enhances the bonding strength between the anti-penetration layer and the energy-absorbing layer.
[0047] Optionally, in S4, the hot-pressing temperature is 60~70℃, the hot-pressing time is 10~15min, and the hot-pressing pressure is 0.5~1.0 MPa to ensure tight bonding between layers; the adhesive is an epoxy adhesive, and the coating amount is 10~20g / m². 2 .
[0048] Optionally, in S5, the dry mixing time is 4±0.5 min, the stirring speed is 100~150 rpm, and after adding the self-healing microcapsules and curing agent, the stirring speed is reduced to 50~80 rpm to prevent the self-healing microcapsules from breaking. When the breakage rate of the self-healing microcapsules exceeds the standard, 5% of the original total amount of self-healing microcapsules is added, and the stirring speed is further reduced to below 40 rpm. Optionally, in S5, high-frequency vibration is performed after casting to improve the bonding strength between the fiber and the matrix interface.
[0049] Optionally, in S5, the curing method is a film curing method, in which a PE film and wet burlap are covered on the surface of the protective structure and cured in an environment of 20~25℃ and RH>90%.
[0050] A typical embodiment of the present invention provides the application of the above-mentioned protective structure containing functionally graded anti-penetration self-healing ultra-high performance concrete. Its multi-layered gradient structure design endows it with excellent anti-penetration, anti-impact, anti-explosion and anti-stripping properties, and can be widely used in military protection engineering and civil protection engineering.
[0051] Example 1 The protective structure in this embodiment is adapted to stress waves, and the interlayer transmission diagram of stress waves is shown below. Figure 3 As shown, as the stress wave propagates layer by layer from top to bottom, the difference in wave impedance guides the compression wave to gradually transform into a tension wave. The energy is slowly released and attenuated in the multi-layer structure, and the impact energy is dissipated and weakened accordingly.
[0052] A protective structure is provided, wherein the concrete consists of five layers from the outside in: a crack-resistant layer, a transition layer, a penetration-resistant layer, an energy-absorbing layer, and a spalling-resistant layer. The layers work together to improve the overall resistance to penetration.
[0053] The raw materials for each layer include the components shown in Table 1 by weight, and the thickness of each layer is shown in Table 1.
[0054] Table 1. Mass fraction and thickness of each layer component in the protective structure
[0055] The cement used is 52.5 grade ordinary Portland cement with a specific surface area of 350~400 m². 2 / kg; The silica fume contains no less than 97% silica by mass, has a pozzolanic activity index greater than 95%, a specific surface area greater than 21.0 m² / g, and a density of 2.20 g / cm³. The fly ash is Class I fly ash, with a loss on ignition of less than 3.0% and a specific surface area greater than 1000 cm² / g. Its main components include silicon dioxide and aluminum oxide. The fine aggregate consists of natural river sand and steel grit in a mass ratio of 7:3. The fineness modulus of the natural river sand is 2.8 and the maximum particle size is 4.75 mm. The density of the steel grit is greater than 7.0 g / cm³ and the particle size range is 0.1~2 mm. The coarse aggregate consists of basalt crushed stone and corundum in a mass ratio of 6:4; the crushing value of the basalt crushed stone is 8%, and the particle size ranges from 5 to 8 mm; the corundum has a Mohs hardness of 9, a density of 4.0 g / cm³, and a particle size of 3 to 5 mm. The length of the hooked steel fiber is 13mm, the diameter is 0.2mm, and the tensile strength is ≥2000MPa; The straight steel fibers come in three lengths: 6mm, 13mm, and 20mm, with a mass ratio of 1:1:1; the tensile strength of the straight steel fibers is ≥2000MPa. The PE fibers are uniformly distributed in length between 6 and 18 mm, in diameter between 10 and 30 μm, and have a tensile strength ≥ 3000 MPa. The self-healing microcapsules are dicyclopentadiene encapsulated in urea-formaldehyde resin, with an average particle size of 150 μm and an average wall thickness of 10 μm. The fiber weight of the geotextile is 300 g / m. 2 ; The hardness (Shore hardness) of the polyurethane elastomer is Shore A 90.
[0056] The self-healing microcapsules are dicyclopentadiene encapsulated in urea-formaldehyde resin, with an average particle size of 200 μm and a wall thickness of 10 μm.
[0057] The PE fiber mesh is 3D woven with a mesh size of 5×5mm, a single filament strength of 2.4Gpa, and an interlayer spacing of 10mm.
[0058] Preparation methods include: S1. Mix cement, silica fume, fly ash, and fine aggregate according to the components in Table 1, and dry mix at 100 rpm for 4 minutes. Then add water and water-reducing agent. During wet mixing, add self-healing microcapsules and curing agent, and mix at 50 rpm until uniform. Then, while maintaining the mixing state, add straight steel fibers in 3 batches, with an interval of 1 minute between each addition. Then, use a vibrating screen to evenly spread PE fibers on the surface of the slurry, and mix at 30 rpm until uniform. After pouring into the mold, turn on the magnetic field orientation device for 5 minutes with a magnetic field strength of 1.2T, and continue for 7 minutes to align the steel fibers in a direction perpendicular to the surface of the protective structure. Then, use a vibrating table to vibrate in two stages. The first stage is vertical vibration to remove large air bubbles, and the second stage is inclined vibration at a 15° angle to promote the three-dimensional orientation of the fibers. The arrangement is used to obtain the crack-resistant layer.
[0059] S2. Before the initial setting of the crack-resistant layer, lay the epoxy resin-impregnated geotextile on the surface of the crack-resistant layer and roll it twice with a pressure of 0.2 MPa. Then, pre-embed basalt short-cut fibers on the surface of the geotextile; wherein the basis weight of the geotextile is 300 g / m². 2 It is pre-impregnated with epoxy resin emulsion and dried at 60°C until touch dry before use, and the thickness of the epoxy resin residue on its surface is about 80μm.
[0060] S3. According to the composition in Table 1, the moistened coarse aggregate and 50% fine aggregate (450 parts) are dry-mixed for 3 minutes. Then, cement, silica fume, fly ash and the remaining fine aggregate are added and dry-mixed evenly. After that, water and water-reducing agent are added and wet-mixed. During the wet-mixing process, hook-shaped steel fibers are added through a vibrating screen. After stirring evenly, it is poured onto the surface of the transition layer. Corundum sand with a particle size of 0.3 mm is used as raw material and pressure sandblasting is performed at 0.6 MPa to embed the corundum sand into the surface of the slurry to form a rough surface with a roughness Ra=50 μm. After sandblasting, nano-clay modified epoxy resin interface agent is sprayed on the surface with a thickness of 200 μm. After spraying, it is cured at 60℃ for 30 minutes to obtain an anti-penetration layer.
[0061] S4. Apply 10g / m² to the lower surface of the energy-absorbing material. 2Apply epoxy adhesive to the surface of the energy-absorbing material and use a hot press to hot press the energy-absorbing material onto the surface of the anti-penetration layer at a temperature of 60°C, and maintain the hot press state for 10 minutes; then apply adhesive to the surface of the energy-absorbing material to obtain the energy-absorbing layer.
[0062] S5. Dry mix cement, silica fume, fly ash, and fine aggregate at 100 rpm for 4 minutes. Then add water and water-reducing agent for wet mixing. Add self-healing microcapsules during wet mixing. After adding the self-healing microcapsules and curing agent, reduce the mixing speed to 50 rpm and mix until uniform. Then pour the obtained slurry onto the energy-absorbing layer. During the pouring process, lay PE fiber mesh so that the PE fiber mesh is located in the middle of the pouring to form an anti-stripping layer. After pouring, perform high-frequency vibration. Use the membrane curing method to cover the surface of the protective structure with PE film and wet burlap and cure in an environment of 20℃ and RH>90% to obtain the protective structure.
[0063] Comparative Example 1 An ultra-high performance concrete is prepared by means of the following raw materials in parts by weight: 500 parts cement, 50 parts silica fume, 50 parts fly ash, 900 parts fine aggregate, 150 parts straight fiber, 125 parts water, and 8 parts water-reducing agent.
[0064] The requirements for each raw material are the same as those for the crack-resistant layer in Example 1; the magnetic field orientation method is not used in the preparation method.
[0065] The thickness of the obtained product is 183 mm, which is the same as the total thickness of Example 1; the difference from Example 1 is that it adopts a single-layer structure, with randomly arranged mixed fibers, and no transition layer or self-healing material.
[0066] Comparative Example 2 A functionally graded concrete (three-layer graded) includes a surface layer (steel fiber reinforced concrete), an intermediate layer (high-strength concrete), and a bottom layer (steel fiber reinforced concrete).
[0067] The raw materials for each layer include the components shown in Table 2 by weight, and the thickness of each layer is shown in Table 2.
[0068] Table 2. Raw materials and parts by weight for each layer of Comparative Example 2
[0069] The requirements for each raw material are the same as those for the crack-resistant layer in Example 1.
[0070] The difference from Example 1 is that: this structure only adopts a three-layer gradient design, without a transition layer and an energy-absorbing layer, the middle layer is made of ordinary high-strength concrete instead of a specially optimized anti-penetration layer, there are no self-healing microcapsules, and the steel fibers are arranged randomly; the preparation method does not use a magnetic field orientation method.
[0071] Comparative Example 3 A functional gradient concrete is composed of a crack-resistant layer, a penetration-resistant layer, and a spalling-resistant layer. The composition and thickness of each layer are the same as in Example 1, but the transition layer and energy-absorbing layer are omitted. Since all three layers are concrete, they are poured directly in the order of thickness direction without considering interlayer connection. PE fiber mesh is still added during the pouring of the spalling-resistant layer.
[0072] Experimental Example The product materials obtained in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 were subjected to conventional mechanical tests and high-speed projectile penetration tests.
[0073] Routine mechanical tests include bending strength tests.
[0074] The test conditions in the method for testing the penetration performance of high-speed projectiles include: preparing the test object as a prismatic target, using a pointed oval projectile with a diameter of 28 mm, and using 30CrMnSiNi2A high-strength alloy steel (yield strength of 1370-1466 MPa, ultimate strength of 1770 MPa, Rockwell hardness of 55 HRC). In the prismatic target, the crack-resistant layer of Example 1 and Comparative Example 3 is the projectile-facing surface, and the surface of the surface layer of Comparative Example 2 is the projectile-facing surface. The test device mainly includes a barrel, a high-speed camera, and a target. The barrel is used to fire bullets to strike the target in front. The bullet impact velocity is set to 400 m / s. The high-speed camera is installed on the side of the trajectory to capture the projectile's motion. Then, the degree of damage to the concrete target by the high-speed projectile is evaluated by measuring the penetration depth, crater diameter, and crater volume of the target.
[0075] The results of conventional mechanical experiments and tests on resistance to high-speed projectile penetration are shown in Table 3.
[0076] Table 3 Results of conventional mechanical tests and tests on resistance to high-speed projectile penetration
[0077] The repair rate in the table is calculated as follows: ; Among them, initial bending strength: the bending strength of the material before it is damaged; Post-repair flexural strength: The flexural strength of the material tested 7 days after it was damaged and self-repaired; Repair rate: This indicates the degree to which the material's bending strength is restored. The closer the value is to 100%, the better the repair effect.
[0078] During the penetration of a high-speed projectile, the impact load propagates within the material as stress waves, undergoing reflection, transmission, and attenuation at different interfaces. A well-designed gradient structure can optimize the stress wave propagation path, allowing the impact energy to dissipate gradually, thereby reducing local stress concentration effects and improving overall protection capabilities.
[0079] The gradient structure has a clear division of functions for each layer, including: Crack-resistant layer: Improves the tensile and crack resistance of the material and has a self-healing function, which can quickly fill micro-cracks and restore strength after impact.
[0080] Transition layer: weakens the continuity of the shock wave and effectively disperses energy transfer.
[0081] Penetration-resistant layer: Enhances the material's impact resistance and effectively prevents projectile penetration.
[0082] Energy-absorbing layer: Reduces the impact transmission to subsequent layers by absorbing and attenuating the energy of shock waves.
[0083] Anti-stripping layer: Reduces damage to the back surface, minimizes spalling, and ensures overall structural stability.
[0084] The experimental data fully validated the superiority of this design. Specific results are as follows: Penetration depth: The penetration depth of Example 1 was only 45 mm, far lower than that of the comparative example group (minimum 55 mm), indicating that the optimization of the gradient structure effectively weakened the impact energy and significantly improved the overall protective effect of the material. Impact surface damage: The impact surface crater area (220 mm²) and volume (1800 mm³) of Example 1 were both smaller than those of the comparative example, indicating that the crack-resistant layer material had less plastic deformation after impact and higher structural stability; Back surface damage: The back surface peeling area (120mm²) and volume (900mm³) of Example 1 are the lowest, indicating that the energy of the shock wave has been effectively dissipated in the energy-absorbing layer and the transition layer, further enhancing the overall protection capability. Self-healing capability: The repair rate of Example 1 reached 88%, indicating that the self-healing system can quickly fill microcracks after impact, restore material strength, significantly extend the service life of the material, and ensure the long-term stability of the structure.
[0085] In summary, this gradient structure design, through clear division of labor and a stepwise energy dissipation mechanism, not only significantly improves the impact resistance of the material, but also enhances the stability and self-healing ability of the structure, providing strong support for the research and development of high-performance protective materials.
[0086] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A protective structure, characterized in that, From the outside in, it includes a crack-resistant layer, a transition layer, a penetration-resistant layer, an energy-absorbing layer, and a spalling-resistant layer; The raw materials for preparing the transition layer include: fiber fabric, 2-3 parts by weight of epoxy resin, and 0.5-1.5 parts by weight of chopped basalt fibers; The energy-absorbing layer is composed of energy-absorbing material; The raw materials for preparing the crack-resistant layer, penetration-resistant layer and spalling-resistant layer include the following components in parts by weight: 360-520 parts cement, 36-52 parts silica fume, 36-52 parts fly ash, 800-1000 parts fine aggregate, 120-130 parts water and 5-10 parts high-efficiency water-reducing agent. The crack-resistant layer also includes 156-312 parts of straight steel fiber, 39-78 parts of PE fiber, and 12-16 parts of self-healing microcapsules; The anti-penetration layer also includes 800-1000 parts of coarse aggregate and 39-78 parts of hook-shaped steel fiber; The anti-peeling layer also includes 12-16 parts of PE fiber mesh and self-healing microcapsules; The direction of the straight steel fibers in the crack-resistant layer is perpendicular to the surface of the protective structure; the straight steel fibers include straight steel fibers with lengths of 6mm, 13mm and 20mm, and the mass ratio of the three is 1:(0.5~1.5):(0.5~1.5). The coarse aggregate includes basalt and corundum in a mass ratio of (5~6):(4~5), wherein the basalt has a particle size of 5~8mm and the corundum has a particle size of 3~5mm. The energy-absorbing material includes one or more of polyurethane elastic materials and nitrile rubber; The self-healing microcapsules are microcapsules formed by encapsulating dicyclopentadiene inside a urea-formaldehyde resin shell, with an average particle size of 50~200μm and a urea-formaldehyde resin shell wall thickness of 5~10μm, forming an impact-triggered self-healing system.
2. The protective structure according to claim 1, characterized in that, The thickness of the crack-resistant layer is 20-50 mm, the thickness of the transition layer is 1-4 mm, the thickness of the penetration-resistant layer is 80-150 mm, the thickness of the energy-absorbing layer is 10-20 mm, and the thickness of the anti-stripping layer is 20-50 mm.
3. The protective structure according to claim 1, characterized in that, The fine aggregate includes natural river sand and steel shot in a mass ratio of (5~7):(3~5).
4. A method for preparing the protective structure according to any one of claims 1-3, characterized in that, Includes the following steps: S1. After dry mixing of cement, silica fume, fly ash and fine aggregate, water and water-reducing agent are added. During wet mixing, self-healing microcapsules are added. After mixing, straight steel fibers and PE fibers are added respectively. The mixture is then poured into a mold to obtain a crack-resistant layer. S2. Before the crack-resistant layer initially sets, the fiber fabric impregnated with epoxy resin is laid on the surface of the crack-resistant layer and rolled. After rolling, basalt short-cut fibers are embedded to obtain a transition layer. S3. After dry mixing the moistened coarse aggregate with fine aggregate, cement, silica fume and fly ash, add water and water-reducing agent. During the wet mixing process, add end-hook steel fibers. After mixing evenly, pour the mixture onto the surface of the transition layer and sandblast to obtain an anti-penetration layer. S4. Apply adhesive to the surface of the energy-absorbing material that is in contact with the anti-penetration layer, then hot-press the energy-absorbing material onto the surface of the anti-penetration layer, and apply adhesive to the surface of the energy-absorbing material to obtain the energy-absorbing layer. S5. Lay a PE fiber mesh on top of the energy-absorbing layer. Dry mix cement, silica fume, fly ash and fine aggregate, then add water and water-reducing agent. Add self-healing microcapsules during wet mixing. Then pour it on top of the energy-absorbing layer to form an anti-stripping layer. Curing is then performed to obtain a protective structure.
5. The method for preparing the protective structure according to claim 4, characterized in that, In S1, after casting, the direction of the straight steel fibers is made perpendicular to the surface of the protective structure by means of magnetic field orientation. The magnetic field strength is 0.5~1.2T and lasts for 5~7 minutes, so that the orientation degree of the straight steel fibers is >85%.
6. The method for preparing the protective structure according to claim 4, characterized in that, In S3, during the sandblasting process, corundum sand with a particle size of 0.3mm is used, and the sandblasting air pressure is not less than 0.6Mpa; after sandblasting, an interface agent is sprayed on the surface of the anti-penetration layer.
7. The method for preparing the protective structure according to claim 4, characterized in that, In S5, the curing method is membrane curing, which involves covering the surface of the protective structure with PE film and wet burlap, and curing in an environment of 20~25℃ and RH>90%.
8. The application of the protective structure according to any one of claims 1-3 in military or civilian protective engineering.
Citation Information
Patent Citations
Anti-penetration and anti-explosion cement-based protective engineering material and preparation method thereof
CN105622018A
Anti-penetration concrete wallboard as well as preparation method and application thereof
CN118997387A
Battlefield vehicle protection device capable of resisting attack of unmanned aerial vehicle and manufacturing method of battlefield vehicle protection device
CN120120915A